Orbital Infection by Saksenaea vasiformis in an Immunocompetent Host - Mingkwan Lumyongsatien; Pimkwan Jaru-ampornpan; Mongkol Uiprasertkul; Dinesh Selva (Case Reports in Ophthalmological Medicine)
Orbital mucormycosis caused by Saksenaea vasiformis is extremely rare. Herein, we report an immunocompetent 22-year-old Thai female who presented with two months of progressive right upper eyelid mass, associated with swelling, redness, and ptosis. She failed to improve despite multiple courses of antibiotic and steroid treatment. Computed tomography (CT) scan showed infiltration involving the upper eyelid and lacrimal gland. Fungal hyphae were revealed by histopathological study. Polymerase chain reaction (PCR) was positive for Saksenaea vasiformis (GenBank: accession number FR687327.1). The patient was successfully treated with surgical debridement, amphotericin B, and oral posaconazole.